(untitled) (International Seven Journal of Multidisciplinary, 2025)
Objective: To analyze the relationship between hypocalcemia and ruminal atony in dairy cows in the immediate postpartum period, evaluating the impacts of this correlation on animal health and productivity, as well as prevention and nutritional management strategies. Postpartum hypocalcemia is a metabolic condition resulting from the abrupt decrease in calcium levels in the peripartum period, impairing muscle contraction and rumen motility. Decreased rumen activity results in secondary digestive and metabolic problems, such as ketosis and abomasal displacement, as well as increasing the risk of postpartum complications, such as retained placenta and metritis. Research indicates that cows with subclinical hypocalcemia are more likely to have rumen atony and lower digestive efficiency, which has adverse consequences on milk production. Early identification of hypocalcemia, through analysis of blood calcium levels, and the adoption of anionic diets during the transition period, are crucial tactics to mitigate its negative effects. In addition, oral or intravenous calcium administration is often suggested to avoid metabolic complications. Understanding the interaction between hypocalcemia and ruminal atony is crucial for the creation of efficient management strategies, with the objective of improving animal welfare and the productive effectiveness of dairy cows.